THE EFFECT OF CONDITIONED MEDIUM ADIPOSE DERIVED MESENCHYMAL STEM CELLS IN UROTHELIAL CARCINOMA CULTURE CELLS VIABILITY - Prasetyo, Suryo; Hidayatullah, Furqan; Bachtiar, Indra; Rachman, Arif; Putri, Indri Lakhsmi; Castiglione, Fabio; Soebadi, Doddy M.; Hakim, Lukman (Indonesian Urological Association, 2021)
Objective: This study aimed to gives a perspective in CM-ADMSCs effect in urothelial bladder cancer viability. Material & Methods: Human bladder cell carcinoma type 5637 was used as the subject of this in vitro study. This study contains four different groups: untreated control group, Culture medium: hADMSCs with 1:1, 1:2, and 1:4 concentration group. Each group consists of 6 replications to prevent bias of the study. Viability was determined with MTT assay methods and evaluation performed after 48 h exposure of conditioned medium. Results: A post hoc test was conducted to analyze the data. The 5637 bladder cancer cell line demonstrated significantly decreased viability after exposure to culture medium: CM-hADMSCs 1:1 (p: 0.002) compared to the negative control group, but there are no significant differences in viability between the control groups with groups that were exposed to culture medium: CM-hADMSCs 1:2 and culture medium: CM-hADMSCs 1:4 with p: 0.480 and p: 0.060 respectively. Conclusion: Decreased viability of urothelial bladder cancer cells after exposure to CM-hADMSCs occurs at a concentration of 1:1 and Dosage addition more than 1:1 concentration doesn’t give any advantages.